CAMERA BRANDING CALON WALIKOTA DI MEDIA SOSIAL (Studi Kasus Pilwakot 2015 Paslon Idris-Pradi) - Dina Andriana; Widarti Widarti; Jusuf Fadilah (J-IKA, 2020)
Abstract This study discusses the case of camera branding conducted by the regional head candidate pair Idris-Pradi on social media as a campaign tool in obtaining votes in PILWAKOT DEPOK 2015. The study uses a qualitative approach with a constructivist paradigm, the nature of descriptive research with the case study research method from Yin. The forms of photo / camera branding can be seen from the use of shooting ranging from shooting, angle of view (angle) shooting, the type of lens used, the focal point used, lighting and prominent coloration in photographs. In addition, the camera branding element in the form of an authentic element and the unique element of the paslon profile also supports the level of electability. The use of photo / camera branding can have direct and indirect effects for voters. And voters in Depok are more of the majority of traditional voter types, although around 37.6% of voters in Depok are of productive age.